PENGARUH JUMLAH ANGGOTA, SIMPANAN, PINJAMAN DAN MODAL KERJA TERHADAP SHU PADA KOPERASI KPRI MITRA KABUPATEN MAJALENGKA - Yelsha Dwi Pasca (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of the number of members, total deposits, total loans and working capital on the acquisition of Business Profits (SHU) in the KPRI Mitra Koperasi of SMA Negeri 1 Maja, Majalengka. The data source uses secondary data, namely financial statement data. The financial report data used in this thesis is data for the last 6 years from 2015 to 2020 at the KPRI Mitra SMA Negeri 1 Maja, Majalengka. The sampling method used in this study, which is more specifically the type or method of non-probability sampling used in this study, is purposive sampling. Based on the results of research that has been done that the correlation coefficient simultaneously (together) between the total of members, deposits, loans, working capital to the remaining operating results, that the R Square is 0.550. This value is the result of the square of the correlation coefficient. The value of Rsquare x 100% is called the coefficient of determination. In this case it means that 55% of the influence of the total of members, total deposits, total of loans, working capital on the remaining operating results. For the rest, (100% - 55% = 45%) caused by other factors that were not studied. The result of interpretation of the coefficient of determination is 55%. Included in the strong or high influence. Based on the results of the F / ANOVA test, Fcount = 4.769 with a significance level of 0.000. As for the value of Ftable = 0.225 at a significance level of 0.05. So that Fcount > Ftable (4.769 > 0.225) with a significance value of 0.000 < 0.05 which indicates a significant regression model. So the conclusion is Fcount > Ftable, then H0 is rejected, meaning the total of members, total deposits, total loan, working capital simultaneously affect the SHU at the Koperasi KPRI Mitra of SMA Negeri 1 Maja, Majalengka.